AFIKS BAHASA MELAYU RIAU DIALEK KAMPAR (Kajian Fungsi dan Makna) - Martius Martius (Lembaga penelitian dan pengabdian kepada Masyarakat, 2015)
In languages agglutination, so that a basic word can be used in a substitutions, the word must first obtain gramatikalisasi process. Bahasa Melayu Riau Kampar is a kind of language agglutination gramatikalisasinya process performed by affixation. This study aimed to describe the form of prefixes and suffixes, see the function prefixes and suffixes, and know the meaning arising from the process and sufiksasi prefiksasi. To achieve these objectives, the authors used data through the method of introspection. Once the data is collected, then analyzed using the methods and techniques distributional vanished. After the data is analyzed, the research concluded that the prefixes in the form BMRK consists of a prefix ma (N) - di-, Perhaps, pa(N) - arms, Ka, and darling. Then the form of the suffix is the suffix -ang -eng, -ong, -in, -un, -i, -ki, -pi, -ti, and an. The function is forming verb affixes, the active verb is transitive, intransitive verb active, passive verbs, and nouns forming.